2013
DOI: 10.1088/0004-637x/765/1/40
|View full text |Cite
|
Sign up to set email alerts
|

The Ionized Circumstellar Envelopes of Orion Source I and the Becklin-Neugebauer Object

Abstract: The 229 GHz (λ1.3 mm) radio emission from Orion-KL was mapped with up to 0. 14 angular resolution with CARMA, allowing measurements of the flux densities of Source I ("SrcI") and the Becklin-Neugebauer Object (BN), the two most massive stars in this region. We find integrated flux densities of 310 ± 45 mJy for SrcI and 240 ± 35 mJy for BN. SrcI is optically thick even at 229 GHz. No trace of the H30α recombination line is seen in its spectrum, although the v 2 = 1, 5(5,0)-6(4,3) transition of H 2 O, 3450 K abo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(71 citation statements)
references
References 42 publications
2
68
1
Order By: Relevance
“…SrcI's flux density is proportional to ν 2 from 43 GHz to 229 GHz, suggesting that the emission is optically thick over this frequency range, but the brightness temperature calculated from the high resolution images is 1500 K, much lower than expected for an HII region. Although these results do not rule out the possibility that SrcI is an exceptionally dense HII region that is not fully resolved by the observations, Plambeck et al (2013) concluded that the continuum most likely originated from electron-neutral free-free emission (the H − opacity), as proposed originally by Reid et al (2007). The H − opacity is important at temperatures below 4500 K where electrons, produced plambeck@berkeley.edu by ionization of Na, K, and other metals, scatter off neutral hydrogen atoms or molecules.…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…SrcI's flux density is proportional to ν 2 from 43 GHz to 229 GHz, suggesting that the emission is optically thick over this frequency range, but the brightness temperature calculated from the high resolution images is 1500 K, much lower than expected for an HII region. Although these results do not rule out the possibility that SrcI is an exceptionally dense HII region that is not fully resolved by the observations, Plambeck et al (2013) concluded that the continuum most likely originated from electron-neutral free-free emission (the H − opacity), as proposed originally by Reid et al (2007). The H − opacity is important at temperatures below 4500 K where electrons, produced plambeck@berkeley.edu by ionization of Na, K, and other metals, scatter off neutral hydrogen atoms or molecules.…”
Section: Introductioncontrasting
confidence: 61%
“…Omitting all the short spacing data greatly reduces the magnitudes of these ripples. (Plambeck et al 2013). Red circles indicate radii of 100, 250, and 850 kλ.…”
Section: Self-calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sources 279 and 308 each have radio spectra that are steeper than n 0.6 . Source 279 is the Becklin-Neugebauer Object, and is thought to be a runaway B star, ejected from a system with Source I (our Source 308) in an explosive event 500 years ago (e.g., Plambeck et al 1995;Gómez et al 2008;Plambeck et al 2013). The BN Object has a spectral dependence of n 1.3 below 100 GHz, above which it flattens, and is suggested to be freefree emission from a dense, hypercompact H II region.…”
Section: Nature Of Detected Sourcesmentioning
confidence: 99%
“…The BN Object has a spectral dependence of n 1.3 below 100 GHz, above which it flattens, and is suggested to be freefree emission from a dense, hypercompact H II region. Source I has a spectral dependence of n 2 and is most easily explained by H − free-free emission in a disk (e.g., Plambeck et al 2013). Both sources have massive stars driving ionizing circumstellar material and driving the free-free emission we detect, explaining their significant fluxes despite their distance from q 1 Ori C.…”
Section: Nature Of Detected Sourcesmentioning
confidence: 99%